2022
DOI: 10.1111/1462-2920.16317
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and diversity of eukaryotic rather than bacterial community relate closely to the trophic level of urban lakes

Abstract: Scientific understanding of biotic effects on the water trophic level is lacking for urban lakes during algal bloom development stage. Based on the Illumina MiSeq sequencing, quantitative polymerase chain reaction (PCR), and multiple statistical analyses, we estimated distribution patterns and ecological roles of planktonic bacteria and eukaryotes in urban lakes during algal bloom development stage (i.e., April, May, and June). Cyanobacteria and Chlorophyta mainly dominated algal blooms. Bacteria exhibited sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Following the end of the nutrient additions the ponds with single or no foundational species revert to their previous physicochemical state whereas the interactive effect of the foundation species stabilizes a new physicochemical state, characterized by a persistent turbid state ( Narwani et al, 2019 ). We hypothesize that this stabilized community state results at least partly from the insensitivity of certain cyanobacteria to filter feeding and allelochemicals ( Pimm, 1984 ), and is possibly mediated by positive interactions between Dreissena and Myriophyllum ( Wan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the end of the nutrient additions the ponds with single or no foundational species revert to their previous physicochemical state whereas the interactive effect of the foundation species stabilizes a new physicochemical state, characterized by a persistent turbid state ( Narwani et al, 2019 ). We hypothesize that this stabilized community state results at least partly from the insensitivity of certain cyanobacteria to filter feeding and allelochemicals ( Pimm, 1984 ), and is possibly mediated by positive interactions between Dreissena and Myriophyllum ( Wan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In more extreme environments, like those with increasing salinity up to hypersaline lakes, heterotrophic bacteria and Archaea thrive while most eukaryotes die out ( Elloumi et al, 2009 ). While it has been suggested that eukaryotic communities have low resistance but high resilience and rapid recovery via dormancy ( Simon et al, 2016 ), it is also possible that the appearance of low resistance and the associated high variance in the community structure may be only due to lower density of eukaryotes in the local environment ( Whitman et al, 1998 ; Caron et al, 1999 ; Lefranc et al, 2005 ; Wan et al, 2022 ), or because of strong top-down regulation of the small eukaryotes by cladocerans and copepods ( Parslow et al, 1986 ; Lepère et al, 2006 ). Additionally, it must be considered that eukaryotic plankton communities often have a distinct separation between stable abundant sub-communities and stochastic rare sub-communities prone to experimental (sequencing noise) and biological (dormancy) artifacts ( Nolte et al, 2010 ; Lynch and Neufeld, 2015 ; Xue et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, stochastic processes or some uninvestigated important environmental variables might contribute to the patterns of the PMA‐treated protistan and fungal communities (Wang et al, 2020). Additionally, deterministic processes may be more important for bacteria than eukaryotes in some freshwater systems (Pearman et al, 2022; Wan et al, 2023). Collectively, relic DNA remaining in waters can obscure the relationships between microbial taxa and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The forward primer 338F (5′-ACT CCT ACG GGA GGC AGC A-3′) and the reverse primer 806R (5′-GGA CTA CHV GGG TWT CTA AT-3′) were employed to amplify the V3-V4 region of bacterial 16S rRNA genes (Mori et al, 2014;Wan et al, 2022). The following PCR procedure was used: 98°C for 5 min, followed by 25 cycles of denaturation at 98°C for 30 s, annealing at 53°C for 30 s, and extension at 72°C for 45 s, with a final extension of 5 min at 72°C.…”
Section: Dna Extraction and 16s Rrna Gene Sequencingmentioning
confidence: 99%